PENGELOLAAN IKLAN LAYANAN MASYARAKAT “JAGA PASOKAN AIR” OLEH HUMAS PDAM TIRTA PAKUAN KOTA BOGOR - Aat Ruchiat Nugraha -; Raden Adi Pratama Putra (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
On July 24, 2019, the Public Relations of the Bogor Municipal Water Supply Company or publicly known as PDAM in Bogor City planned on making a public video advertising program for the first time with "dry season” as the theme. It was explained that in the millennial era, messages were delivered in various forms of information, such as media printing, online and websites that were created in different forms. At the beginning, Public Service Advertisment was presented in the form of infographics. Currently, PSA made a video in order to make it more interesting. The purpose of the study were: to describe the creation of a public service advertisement for "Jaga Pasokan Air" of the PDAM in Bogor City , describe the content and message of the public service advertisement for "Jaga Pasokan Air" of the PDAM in Bogor City, describe and explain the use of social media about the advertisement of the "Jaga Pasokan Air" public service of the PDAM in Bogor City. The method of this study was using a descriptive method. Based on the results of research conducted, the informant gave an explanation of the situation behind the management of Public Service Advertisement, the meaning of the title "Jaga Pasokan Air" and publications on social media. The Public Relations of PDAM in Bogor City have carried out a plan and systematic process even though it is complicated in the process. The conclusion took a long time up to 2 months and the manufacturing process is quite complicated because it requires careful preparation so that the results can be accounted for. Some further advices are managing public service advertisements in the form of videos should continue to be done periodically because after the creation of Public Service Advertisement for the first time there is no exact realization in making the next PSAs that at first was planned once every month. Many programs are planned for the next days but never get into the realization and so it’s just stuck on the process